Learning Deficiencies Among Adult Inmates, 1982: Louisiana, Pennsylvania, and Washington - Bell, Raymond ([Verlag nicht ermittelbar], 1985)
The National Institute of Justice sponsored this study of 1,065 prison inmates in Louisiana, Pennsylvania, and Washington. Respondents were administered an academic achievement test, the Tests of Adult Basic Education, and an individual intelligence test, the Wechsler Adult Intelligence Scale-Revised (WAIS-R). Other screening tests were also given to certain respondents, including the Mann-Suiter Disabilities Screening Test and the Adaptive Behavior Checklist. Data for each inmate includes offenses committed, prior institutionalization, juvenile adjudication, years of formal education, academic and vocational participation while incarcerated, previous diagnoses, childhood home situation, death of parents, number of siblings, and any childhood problems. Information on demographic characteristics, such as age, sex, race, employment history, and physical condition, is available for each respondent.